Effects of the growth regulators for the induction of somatic embryos from different explants of Echinocactus parryi Engelm., an endemic and endangered species - Osuna Avila, Pedro (2021)
Introduction: The list of threatened species is enhancing and needs to integrate plant tissue culture tools with conventional techniques that support the appropriate management of these species. Objective: To assess the effects of the growth regulators for the induction of somatic embryos from explants of Echinocactus parryi Engelm. Materials and methods: A completely randomized design was utilized to evaluate three types of explants (mature seeds, shots and green callus) cultured on basal Murashige & Skoog media (MS) with different growth regulators concentrations (2, 4-D [dichlorophenoxy acetic acid], BAP [6-benzylaminopurine] and kinetin). Histological analysis of the embryogenic structures was performed. Results and discussion: The auxin 2, 4-D induced both embryogenic and organogenic callus from seeds and shoot explants. The globular stage did not evolve to their maturity, presumably because of 2, 4-D accumulation. The compact callus explants were the more efficient to induce 19.2 somatic embryos per explant when they were cultured in the medium with 0.5 mg∙L-1 kinetin. However, the latest phases did not germinate, probably due to abnormalities generated by genetic and epigenetic changes in the DNA that can cause abnormal somatic embryos. The histology image demonstrated that the globular and torpedo structures were visible under a microscope showing stained nucleus and numerous starch grains. Conclusions: E. parryi is a species that can produce a high number of embryogenic structures, which represents a great potential to grow massive plants.